Optimalisasi Proses Administrasi, Pengelolaan Fasilitas Serta Permintaan Logistik PT X Dengan Metode Work Breakdown Structure - Sabrina Salma Nabila; Rusindiyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Administrative process optimization is a systematic effort to improve efficiency, productivity, and quality in the execution of administrative tasks within the company, while facilities management and demand for goods and logistics focus on improving operational efficiency and effectiveness, which will apply the WBS method to decompose complex tasks into more manageable components. This analysis is expected to increase visibility, engagement, and understanding of each stage in the administrative, facilities management, and logistics management processes, enabling more targeted and impactful change implementation. Overall, this research is geared towards achieving improved performance and efficiency at PT X through the application of WBS methodology in the context of the company's administration and logistics